Nanozyme catalyzed cascade reaction for enhanced chemodynamic therapy of low-H2O2 tumor. (March 2022) - Jiang, Chao; He, Ting; Tang, Qinan; He, Jin; Ren, Qiaoju; Zhang, Dong-Yang; Gurram, Bhaskar; Blum, Nicholas Thomas; Chen, Yunzhi; Huang, Peng; Lin, Jing
Highlights: A hybrid nanozyme (MMF-Au) composed of ultrasmall gold nanoparticles (Au NPs) and melanin-coated manganese dioxide flowers (MMF) was developed. The MMF-Au nanozyme could trigger the cascade reaction of glucose oxidation and Fenton-like reaction. The MMF-Au was used for enhanced CDT of low-level H2 O2 tumors under the guidance of MRI and PAI. The MMF-Au has a great potential for cancer theranostics. Abstract: The efficacy of chemodynamic therapy (CDT) is strongly dependent on the hydrogen peroxide (H2 O2 ) level of tumor tissues. Nanozyme-mediated glycolysis reaction is considered as a promising way to supply the amount of H2 O2 in situ, therefore, the development of nanozyme-based CDT platform is desirable for low-H2 O2 tumor treatment. Herein, we developed a hybrid nanozyme (denoted as MMF-Au) composed of ultrasmall gold nanoparticles (Au NPs) and melanin-coated manganese dioxide flowers (MMF) for enhanced CDT of low-level H2 O2 tumors under the guidance of magnetic resonance imaging (MRI) and photoacoustic imaging (PAI). The MMF-Au nanozyme could trigger the cascade reaction of glucose oxidation and Fenton-like reaction. First, the ultrasmall Au NPs with glucose oxidase (GOx)-mimic activity could catalyze the oxidation of glucose to generate large amount of H2 O2 . Subsequently, the H2 O2 was converted into highly toxic hydroxyl radicals (OH) via a Mn 2+ -mediated Fenton-like reaction, due to the release of Mn 2+ during the decomposition of MMF in tumor acid microenvironment. Meanwhile, the released Mn 2+ could perform T 1 -weighted MRI. Additionally, the MMF-Au could be used for PAI and photothermal therapy (PTT) due to the strong absorption of melanin in the near-infrared (NIR) region. Both in vitro and in vivo experimental results demonstrated that nanozyme catalyzed cascade reaction could achieve better CDT efficacy in tumors with low level of H2 O2 . This study provided a promising strategy to construct nanozyme-triggered cascade reaction system against low-level H2 O2 tumors. Graphical abstract: A hybrid nanozyme (MMF-Au) was develpoed to trigger catalytic cascade reaction of glucose oxidation and Mn 2+ -mediated Fenton-like reaction for enhanced chemodynamic therapy of low-level H2 O2 tumors under the guidance of magnetic resonance imaging and photoacoustic imaging. Image, graphical abstract .